Applying Lean Maintenance to Optimize Manufacturing Processes in the Supply Chain: A Peruvian Print Company Case - Edgar D. Ramos; Ron Mesia; Cesar Alva; Rudy Miyashiro (International Journal of Supply Chain Management, 2020)
High competitiveness forces companies to reduce their costs and optimize their processes throughout their supply chain. One of these supply chain processes is manufacturing, where the objective may be that the machines work at their maximum efficiency and capacity. This research proposes to increase the effectiveness of the printing process by improving the maintenance applying the Lean concepts. The research will serve as a guide for other companies in the printing industry that seek to increase their production based on the effectiveness of their equipment focused on maintenance processes, which is an important component in their supply chain manufacturing.